Peppermint oil prevented oxidative stress in experimental animal – induced acute single bout of eccentric exercise (ASBEE): study on blood catalase and hydrogen peroxide (H2O2) and glucose transporter-4 (GLUT-4) expression on the muscle cells - Dewi Aryanti; Denny Agustiningsih; Mae Sri Hartati Wahyuningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Peppermint oil is one of the essential oils with antioxidant activity that can reduce levels of reactive oxygen species (ROS). An acute single bout of eccentric exercise (ASBEE) is an acute exercise activity that can lead to increased ROS and cause skeletal muscle injury. This study aimed to assess the effect of peppermint oil in experimental animals induced with ASBEE with the purpose to measure catalase, hydrogen peroxide (H2O2) blood and glucose transporter-4 (GLUT-4) expression of skeletal muscle cells. A total of 30 Wistar rats (Rattus norvegicus) aged 20-24 weeks, weighing 160-350 g were divided into six groups i.e. T1 (n =5), T2 (n =4) and T3 (n =5) given peppermint oil orally at different dose of 0.25, 0.5 and 1.0 g/kg, respectively, one hour before inducing with ASBEE; C0 (n=5) not given peppermint oil and not induced with ASBEE; CA (n=5) not given peppermint oil and induced with ASBEE and CE (n=5) given vitamin E 400 mg/kg one h before induced with ASBEE. ASBEE induction was done by downhill running on a rat treadmill -50 with a load index of 70% VO2 max for 30 min. Twenty four h after induction of ASBEE, blood samples and muscle tissue were taken for examination of catalase, H2O2 and GLUT-4 expression. The results showed increased levels of blood catalase and decreased blood H2O2 levels in groups T1, T2, T3, and CE. The opposite occurred in the group CA. The GLUT-4 expression did not show any significant difference between groups. It was concluded that peppermint oil can improve the condition of oxidative stress caused by ASBEE.